2011
DOI: 10.1021/pr101124f
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of theCaenorhabditis elegansOocyte

Abstract: Oocytes were purified from the temperature-sensitive fertilization-defective fer-1(b232ts) mutant of the nematode Caenorhabditis elegans and used for comprehensive mass spectrometric analysis. Using stringent criteria, 1165 C. elegans proteins were identified; at lower stringency, an additional 288 proteins were identified. We validate the high degree of sample purity and evaluate several possible sources of bias in the proteomic data. We compare the classes of proteins identified in the current oocyte proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In addition, proteomic studies of sea urchin eggs showed that in the first 2 minutes after fertilization the number of protein spots detectable by 2D gel electrophoresis decreases by 23%, suggesting that translation of new proteins is a relatively “late” event of egg activation (Horner and Wolfner, 2008; Roux et al, 2006). Characterization of the C. elegans oocyte proteome and transcriptome shows that the oocyte proteome appears to be biased towards factors likely to act immediately upon fertilization while the oocyte transcriptome is biased towards factors that are likely to act later in embryogenesis (Chik et al, 2011). These findings point to maternal proteins playing key roles in the initial events of egg activation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, proteomic studies of sea urchin eggs showed that in the first 2 minutes after fertilization the number of protein spots detectable by 2D gel electrophoresis decreases by 23%, suggesting that translation of new proteins is a relatively “late” event of egg activation (Horner and Wolfner, 2008; Roux et al, 2006). Characterization of the C. elegans oocyte proteome and transcriptome shows that the oocyte proteome appears to be biased towards factors likely to act immediately upon fertilization while the oocyte transcriptome is biased towards factors that are likely to act later in embryogenesis (Chik et al, 2011). These findings point to maternal proteins playing key roles in the initial events of egg activation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also generated the following relevant transcriptomes: maternal RNAs, which can be used as a proxy for a subset of oogenic RNAs (Baugh et al 2003); germline-specific RNAs obtained from gonads extracted from adult wild-type hermaphrodites and subjected to serial analysis of gene expression (SAGE) (Wang et al 2009); and RNAs in isolated mature sperm (Ma et al 2014). In addition, a study identified several hundred mRNAs whose expression depends on the sperm-specific transcription factor SPE-44 (Kulkarni et al 2012); a proteomics study discovered proteins in isolated mature oocytes (Chik et al 2011); and RNA immunoprecipitation studies identified RNAs associated with RNA-binding proteins in adult oogenic germlines [FBF-1 (Kershner and Kimble 2010); GLD-2 and RNP-8 (Kim et al 2010); GLD-1 (Jungkamp et al 2011); EFL-1 and DPL-1 (Kudron et al 2013)]. However, the classic analysis of Reinke et al (2004) remains the only dataset available focusing on spermatogenic vs. oogenic transcriptomes.…”
mentioning
confidence: 99%
“…Proteome maps are useful representations of the complex "building plan" of a biological system and also serve as valuable tools for the discovery of new cellular functions (2,3). Proteomic studies of single cell populations isolated from a variety of multicellular organisms have recently been achieved, including the oocytes of worms and mice (4)(5)(6); pollen grains (consisting of two sperm and one vegetative cell) and stomatal guard cells of plants (7,8); and sperm cells of mice and flies (9,10). These cell types were relatively accessible because they either reside on the surface and can be purified in large quantities using biochemical fractionation (e.g., guard cells) or are large and can easily be collected (e.g., Caenorhabditis elegans oocytes).…”
mentioning
confidence: 99%